2017
DOI: 10.1007/s40544-017-0147-9
|View full text |Cite
|
Sign up to set email alerts
|

Finger pad friction and tactile perception of laser treated, stamped and cold rolled micro-structured stainless steel sheet surfaces

Abstract: Tactile perception is a complex system, which depends on frictional interactions between skin and counter-body. The contact mechanics of tactile friction is governed by many factors such as the state and properties of skin and counter-body. In order to discover the connection between perception and tactile friction on textured stainless steel sheets, both perception experiments (subjective) and tactile friction measurements (objective) were performed in this research. The perception experiments were carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Based on the above results, we can conclude that the Mach-Zehnder vibro-perception system possesses the characteristics of high sensitivity compared with OPLL vibro-perception system in the direct contact experiment. This high sensitivity is consistent with skin perception in light touch regime that is defined by force less than 1 N [ 38 ]. However, the Mach-Zehnder system has low susceptibility to beating interference for both tapping and sliding motions.…”
Section: Resultssupporting
confidence: 81%
“…Based on the above results, we can conclude that the Mach-Zehnder vibro-perception system possesses the characteristics of high sensitivity compared with OPLL vibro-perception system in the direct contact experiment. This high sensitivity is consistent with skin perception in light touch regime that is defined by force less than 1 N [ 38 ]. However, the Mach-Zehnder system has low susceptibility to beating interference for both tapping and sliding motions.…”
Section: Resultssupporting
confidence: 81%
“…An important point in industrial design and manufacturing is pleasant touching. It has been reported that there is a correlation between tactile friction and the touch comfort level [36]. The results of the current study showed that the type of friction also affected brain dynamics and, consequently, the tactile friction perception.…”
Section: Discussionsupporting
confidence: 53%
“…The tactile friction (also known as skin friction) can be influenced by factors such as material properties of skin, surface texture, resulting contact area, and normal load. These factors are well-formulated as a two-term friction model, which consists of the adhesive component and deformation component of skin friction, as follows [ 11 , 12 ]: where is the total friction force; is the adhesive component of friction; is the deformation component of friction; is the interfacial shear strength; is the real contact area; is the viscoelastic loss fraction; δ is the indentation of the skin; is the applied load; and a is the contact radius of the fingertip, which can be determined as follows: where R is the radius of the fingertip; E* is the effective Young’s modulus; and are the Young’s moduli of the finger and counter-surface; and and are the Poisson’s ratios of the finger and counter-surface, respectively.…”
Section: Resultsmentioning
confidence: 99%